FAKTOR-FAKTOR YANG MEMPENGARUHI PERAN PENJUAL KOMODITAS HORTIKULTURA OLEH KAUM IBU DALAM MENINGKATKAN EKONOMI KELUARGA DI PASAR WAMANGGU KOTA MERAUKE - Nurdhaiyah Nurdhaiyah; David Oscar Simatupang; Untari Untari (Musamus Journal of Agribusiness, 2019)
This study aims to find out how much the factors of education, capital, and dependents influence the role of mothers in improving the family economy in Wamanggu Market and analyze the dominant factors that influence the role of mothers in improving the family economy in Wamanggu Market. This research was conducted at the Wamanggu Merauke Market, for four (4) months, namely from August to December 2018. The population in this study were all vegetable sellers in the Wamanggu Merauke Market. The sampling technique was random sampling with 173 samples and a total population of 63 sellers, while data analysis was carried out with quantitative descriptive analysis method using multiple linear regression analysis. The results of multiple regression analysis show that the magnitude of the effect of education on income (Y): based on education (X1) affects income (Y) insignificantly by 0.044 or 4.4%, based on capital (X2) affects income (Y) significantly by 0.919 or 91.9%, based on dependents (X3) affect income (Y) not significantly by 0.005 or 5%. The dominant factor that influences the decision of mothers in improving the family economy is the capital factor (X2) which is equal to 0.919 or 91.9%. Keywords: Education, Capital, Dependents, Income.